2015
DOI: 10.1002/pola.27571
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical properties of σ–π conjugated organic–inorganic hybrid gels

Abstract: Organic-inorganic hybrid gels containing Si-vinylene units have been synthesized by a hydrosilylation reaction of trior tetra-ethynyl aryl compounds, 1,3,5-triethynylbenzene (TEB), 3,3 0 ,5,5 0 -tetraethynylbiphenyl (TEBP), or tetrakis(4-ethynylphenyl)-methane (TEPM), and bisdimethylsilyl compounds, 1,1,3,3-tetramethyldisiloxane (TMDS) or 1,4-bisdimetylsilylbenzene (BDMSB), in toluene. Network structure of the resulting gels was quantitatively characterized by a scanning microscopic light scattering. The react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We have been developed joint‐liker type gels, which are formed by addition reactions of multifunctional symmetrical molecules as joint and bifunctional molecules as linker in some solvents. The joint‐liker type gels formed homogeneous network structure, and their mesh size could be controlled by the length of the linker molecules . The mesh of the network structure was usable for isolate incorporation of small molecules .…”
Section: Introductionmentioning
confidence: 99%
“…We have been developed joint‐liker type gels, which are formed by addition reactions of multifunctional symmetrical molecules as joint and bifunctional molecules as linker in some solvents. The joint‐liker type gels formed homogeneous network structure, and their mesh size could be controlled by the length of the linker molecules . The mesh of the network structure was usable for isolate incorporation of small molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Neckers et al reported synthesis of Si containing unsaturated star polymers by hydrosilylation reaction of 1,3,5-triethynylbenzene (TEB) and (p-(dimethylsilyl)phenyl)acetylene (Wang, Kaafarani, & Neckers, 2003). Some organic-inorganic hybrid gels containing σ-π conjugated Si-vinylene units in the network were developed in our laboratory by the hydrosilylation reaction of TEB and 1,1,3,3-tetramethyldisiloxane or 1,4-bisdimetylsilylbenzene in toluene (Naga, Iwashita, Nagino, Miyanaga, & Furukawa, 2015). Although, the hydrosilylation reaction is one of the effective methods to synthesize the network structures containing Si-vinylene units, the multifunctional ethynylene compounds, such as TEB, should be necessary.…”
Section: Introductionmentioning
confidence: 99%